2010
DOI: 10.1002/rcm.4507
|View full text |Cite
|
Sign up to set email alerts
|

Improved detection of reactive metabolites with a bromine‐containing glutathione analog using mass defect and isotope pattern matching

Abstract: Drug bioactivation leading to the formation of reactive species capable of covalent binding to proteins represents an important cause of drug-induced toxicity. Reactive metabolite detection using in vitro microsomal incubations is a crucial step in assessing potential toxicity of pharmaceutical compounds. The most common method for screening the formation of these unstable, electrophilic species is by trapping them with glutathione (GSH) followed by liquid chromatography/mass spectrometry (LC/MS) analysis. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 39 publications
0
45
0
Order By: Relevance
“…Detection of 39-and 49-demethylated TMP glutathione or NAC adducts in vitro and in vivo implies that 39-desmethyl-and 49-desmethyl-TMP undergo further oxidation, leading to reactive intermediates (Leblanc et al, 2010;van Haandel et al, 2014). Subsequent bioactivation of stable, primary metabolites to reactive intermediates has been demonstrated with other drugs commonly associated with IADRs, such as phenytoin and carbamazepine (Cuttle et al, 2000;Pearce et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Detection of 39-and 49-demethylated TMP glutathione or NAC adducts in vitro and in vivo implies that 39-desmethyl-and 49-desmethyl-TMP undergo further oxidation, leading to reactive intermediates (Leblanc et al, 2010;van Haandel et al, 2014). Subsequent bioactivation of stable, primary metabolites to reactive intermediates has been demonstrated with other drugs commonly associated with IADRs, such as phenytoin and carbamazepine (Cuttle et al, 2000;Pearce et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…A number of derivatives of GSH such as GSH ethyl ester, dansyl-GSH, brominated GSH, or quaternary ammonium GSH have also been utilized to facilitate MS detection or quantitation [13][14][15][16]. Introduction of stable isotope-labeled GSH analogues such as 13 C 2 15 N-GSH into an incubation medium provides GSHtrapped reactive metabolites with unique isotope patterns that can be used either in isotope pattern-dependent scan or post-acquisition data mining [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, detection of GSH and CN adducts of reactive metabolites by HR-MS relays on characteristics of protonated molecules of the adducts, including their predictable ranges of mass defects or unique isotope patterns. In addition, background subtraction processing that extracts ion species present in accurate full MS spectra of a test samples but not in a control samples is applied for detection of GSH adducts in vitro and in animals [15,20,28]. Recently, Barbara et al reported a LC-time-offlight (TOF) MS E post-acquisition data mining method for reactive metabolite screening.…”
Section: Introductionmentioning
confidence: 99%
“…The resulting gSH conjugates were detected by the presence of a unique doublet isotopic peak with m/z differences of 3 Da in the mass spectra [13,14]. Leblanc et al improved selectivity by using a brominated analog of gSH, N-(2-bromocarbobenzyloxy)-gSH, for in vitro screening of reactive metabolites [15]. The incorporation of bromine in the trapping agent provided a distinct isotope pattern ( 79 br: 81 br = 1:1).…”
Section: Traditional Liquid Chromatography-tandem Mass Spectrometry (mentioning
confidence: 99%
“…Therefore, IPF can potentially be very useful for detecting gSH adducts when a mixture of gSH and 13 c 2 -15 N-labeled gSH is used at a fixed ratio to trap reactive metabolites generated in microsomal incubations [14,37]. Similarly, it is capable of searching gSH adducts when a brominated analog of glutathione, N-(2-bromocarbobenzyloxy)-gSH, is employed as a trapping agent in in vitro incubations [15]. IPF can be applied to selectively detect cyanide-trapped reactive iminium ions when a mixture of stable-isotope-labeled K 13 c 15 N and natural KcN is used as trapping agent [38], and methoxylamine-trapped reactive aldehyde when a mixture of methoxylamine and methoxyl-d 3 -amine is used in the incubations with liver microsomes.…”
Section: Isotope Pattern Filtermentioning
confidence: 99%